2009
DOI: 10.1007/s11239-009-0368-5
|View full text |Cite
|
Sign up to set email alerts
|

Human platelet alloantigens HPA-1, HPA-2, and HPA-3 polymorphisms associated with extent of severe coronary artery disease

Abstract: The contribution of human platelet antigen (HPA)-1 (GPIIb/IIIa), HPA-2 (GPIb/IX), and HPA-3 (GPIIb/IIIa) polymorphisms to the risk of coronary artery disease (CAD) was investigated in 341 CAD patients and 316 matched control subjects. HPA genotyping was performed by PCR-SSP. Regression analysis was employed in assessing the contribution of these variants to CAD risk. The frequency of HPA-1b (P = .009) and HPA-3b (P = .004) alleles, and HPA-1a/1b (P = .045), HPA-1b/1b (P = .007), and HPA-3b/3b (P = .008) genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
1
6
1
1
Order By: Relevance
“…Our study is also consistent with a recent Tunisian study that reported the association of haplotypes containing HPA-1b allele, such as 1b/2a/3a and 1b/2a/3b with CAD risk. This association was still significant when it was adjusted for the traditional risk factors involved in the CAD development [19]. Our findings are in line with the results of prior research performed by Floyd et al in the UK.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study is also consistent with a recent Tunisian study that reported the association of haplotypes containing HPA-1b allele, such as 1b/2a/3a and 1b/2a/3b with CAD risk. This association was still significant when it was adjusted for the traditional risk factors involved in the CAD development [19]. Our findings are in line with the results of prior research performed by Floyd et al in the UK.…”
Section: Discussionsupporting
confidence: 93%
“…It appeared that the relative effect of this polymorphism is decreased considerably with increasing in age and the presence of risk factors, such as blood pressure, diabetes, and cholesterol [20]. Nevertheless, our results are in apparent disagreement with previous reports indicating a positive association of HPA-1b and HPA-3b alleles with the risk of CAD in Tunisian patients [19], platelet hyper-reactivity in ACS [21,22], and increased thrombotic complications [8,23,24].…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…To mimic exposure to β3 or GPIbα during conception, Itgb3 -/-and Gp1ba -/-both active and passive (postnatal antisera injections) murine models of FNAIT. As GPIbα is not constitutively expressed on ECs and anti-GPIbα antibody (i.e., anti-HPA-2a) is involved in FNAIT (36, 37), we used our anti-GPIbα-mediated FNAIT model as a control (37)(38)(39). Our findings demonstrate that antiplatelet β3, but not anti-GPIbα antibodies, impaired angiogenic signaling, inhibited angiogenesis, and induced ICH in the brain of murine fetuses and neonates, and this could be prevented by administration of intravenous immunoglobulin (IVIG) to the mother.…”
Section: Resultsmentioning
confidence: 99%
“…Highly polymorphic distribution of HPA-2 among populations is one of the main factors affecting platelet function. Abboud et al (2010) found that the HPA-2 gene is not only an independent risk factor for coronary heart disease, but also correlates significantly with its severity. Nevertheless, Nomura et al (2006) found no significant difference in HPA-2 between T2DM patients, with or without atherosclerosis, and healthy people.…”
Section: Discussionmentioning
confidence: 95%